2020
DOI: 10.3390/s20030927
|View full text |Cite
|
Sign up to set email alerts
|

Are Inductive Current Transformers Performance Really Affected by Actual Distorted Network Conditions? An Experimental Case Study

Abstract: The aim of this work is to assess whether actual distorted conditions of the network are really affecting the accuracy of inductive current transformers. The study started from the need to evaluate the accuracy performance of inductive current transformers in off-nominal conditions, and to improve the related standards. In fact, standards do not provide a uniform set of distorted waveforms to be applied on inductive or low-power instrument transformers. Moreover, there is no agreement yet, among the experts, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…A notable feature is that, according to this representation, the behavior at the fundamental component is not affected by the presence of other harmonics in the primary current. This peculiarity is often exploited during the study of conventional instrument transformers; it is confirmed by the experimental results presented in many works and specifically addressed by [32]. (6) can be rewritten as:…”
Section: Hd Compensation Techniquementioning
confidence: 59%
“…A notable feature is that, according to this representation, the behavior at the fundamental component is not affected by the presence of other harmonics in the primary current. This peculiarity is often exploited during the study of conventional instrument transformers; it is confirmed by the experimental results presented in many works and specifically addressed by [32]. (6) can be rewritten as:…”
Section: Hd Compensation Techniquementioning
confidence: 59%
“…However, there is an opposite opinion. In particular, in [7], by reproducing the real current curves through the transformer and estimating the total error, it was found that the non-sinusoidal current has an insignificant effect on the measurement accuracy (the error did not exceed the allowable one for the accuracy class). Temperature and magnetic properties of the core are also indicated as essential factors [8].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…It should be emphasized that due to the non-linear shape of the magnetizing characteristic of the magnetic core, the transformation accuracy of the inductive CT depends on the value of the magnetic flux density and thus on the RMS values of the primary current harmonics and the load on the secondary winding [1], [3], [4], [19], [23]. The paper [5] presents analyses on the transformation accuracy of inductive CTs under real operating conditions in a distribution grid. According to the authors, the distortion of the primary current has little influence on their values of current error and phase displacement and may be neglected.…”
Section: Introductionmentioning
confidence: 99%